2021
DOI: 10.1038/s42003-021-02287-8
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming signal transduction through a designer receptor tyrosine kinase

Abstract: Controlling signal transduction with artificial designer receptors is a promising approach to realize future medicine for intractable diseases. Although several functional artificial receptors have been reported by domain engineering, more sophisticated engineering within domains has yet to be thoroughly investigated. Here we demonstrate motif-based engineering of a receptor tyrosine kinase for reprogramming signal transduction. We design a scaffold-less tyrosine kinase domain that does not recruit any signal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…2 c). The result is consistent with our recent study showing that STAT3 or STAT5, but not STAT1, promotes proliferation of Ba/F3 cells 25 , 26 . These results indicate that the engineered receptor scaffold activates signaling molecules bound to the tyrosine motif in response to the synthetic ligand AP20187.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…2 c). The result is consistent with our recent study showing that STAT3 or STAT5, but not STAT1, promotes proliferation of Ba/F3 cells 25 , 26 . These results indicate that the engineered receptor scaffold activates signaling molecules bound to the tyrosine motif in response to the synthetic ligand AP20187.…”
Section: Resultssupporting
confidence: 94%
“…The signaling analyses of the selected tyrosine motif clones demonstrated that proliferation-inducing signaling molecules such as STAT5, MEK, and Akt were activated in both Ba/F3 and 32Dcl3 cells. As shown in our previous study, proliferation of Ba/F3 cells is promoted by STAT3 or STAT5 25 , 26 . The introductory experiments (Fig.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…However, we never know how much levels the signaling molecules should be phosphorylated for cell proliferation. Our previous studies using chimeric receptors demonstrated that Ba/F3, which is a host cell line of THROPPIS, proliferated when either MEK, STAT3, or STAT5 was activated Kongkrongtong et al, 2021). In addition, the chimeric receptors in THROPPIS are not embedded in the membrane but expressed in the cytosol, which means that the signaling pathways could be different from those of the natural receptor TPOR.…”
Section: Throppis Can Be Extended To Other Receptorsmentioning
confidence: 99%
“…Particularly, iCasp9, an inducible suicide gene, has progressed to Phase I clinical trials as a safety switch in cell therapy 17 . In addition, we previously developed designer receptors that can activate target signaling molecules by appropriately arranging domains and tyrosine motifs 18 20 . Such a designer receptor was also utilized for phenotypic screening of tyrosine motifs that efficiently induce cell proliferation 21 .…”
Section: Introductionmentioning
confidence: 99%